RISK MANAGEMENT IN THE JABODEBEK LRT (LIGHT RAIL TRANSIT) DEVEL-OPMENT PROJECT, IN JAKARTA AND ITS NEIGHBOURING CITIES - Trijeti Trijeti; Andi Madeppungeng; Rachmat Said Rasul; Rachmad Irwanto (University Of Muhammadiyah Jakarta, 2022)
LRT (Light Rail Transit) is one solution for an environmentally friendly transportation system to overcome congestion problems that occur in Jakarta. This mass transportation is considered effective because there is less land in the capital for road construction. The project is a complex project that includes design, material procurement and construction. The development that is currently underway is cross-service 1 (Cawang-Cibubur), cross-service 2 (Cawang-Dukuh Atas) and cross-service 3 (Cawang-Bekasi East). This study aims to determine the risks that often arise and find out the right way to handle the risks that arise in the construction of the JABODEBEK LRT project. Data was collected using a questionnaire on 45 respondents who were involved in the construction of the JABODEBEK LRT project. The variables studied in this study are aspects of scheduling planning, aspects of scope and work documents (contracts), aspects of organizational systems, coordination and communication, aspects of resource readiness/preparation, aspects of inspection systems, work control and evaluation and other aspects (force majeure /beyond the ability of the owner and contractor). Data processing in this study used the SPSS version 25 program. This study discusses seven variables classified as high risk (H) in the project.